Bede : a biblical miscellany - Beda Venerabilis, asi 672-735 (Translated texts for historians ;, 1999)
This volume contains six of Bede’s shorter biblical writings, most of which appear here in translation for the first time – On Tobias, On the Resting Places, Thirty Questions on the Book of Kings, On Eight Questions, On the Holy Places and the letter On What Isaiah Says. Taken together, they reveal his amazing versatility as a biblical exegete.